2006
DOI: 10.1002/nur.20154
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to “Doing-the-month” practices is associated with fewer physical and depressive symptoms among postpartum women in Taiwan

Abstract: According to traditional Chinese custom, women should be confined to home and assisted with tasks for 1 month after giving birth to a child. This restrictive regimen is referred to as doing-the-month. The objectives of this study were to describe adherence to doing-the-month practices and to explore the association between adherence to doing-the-month practices and physical symptoms and depression among postpartum women in Taiwan. Participants were 202 women at 4-6 weeks after delivery. Adherence to doing-the-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
128
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(135 citation statements)
references
References 14 publications
5
128
1
1
Order By: Relevance
“…However, Gaillard et al (2014) did not report similar finding. Other factors, such as lack or non-initiation of breastfeeding (Chien et al, 2006;Green et al, 2006;Mosack and Shore, 2006;Lau and Chan, 2007;Baker and Oswalt, 2008;Davey et al, 2011;Sword et al, 2011;Watkins et al, 2011;Figueiredo et al, 2013;Hahn-Holbrook et al, 2013), parity (Green et al, 2006;Glavin et al, 2009;Hamdan and Tamim, 2011;Kozinszky et al, 2011;Sword et al, 2011;Raisanen et al, 2013;Gaillard et al, 2014) and sex of baby (Boyce and Hickey, 2005;de Tychey et al, 2008;Kim et al, 2008;Koutra et al, 2014) showed mixed findings. Women whose infants had medical illnesses (Green et al, 2006;Ueda et al, 2006;Kim et al, 2008;Raisanen et al, 2013), are born prematurely (Raisanen et al, 2013) and are temperamentally difficult (McGrath et al, 2008;Eastwood et al, 2012) are likely to experience postpartum depression.…”
Section: Obstetric and Pediatric Factorsmentioning
confidence: 79%
See 2 more Smart Citations
“…However, Gaillard et al (2014) did not report similar finding. Other factors, such as lack or non-initiation of breastfeeding (Chien et al, 2006;Green et al, 2006;Mosack and Shore, 2006;Lau and Chan, 2007;Baker and Oswalt, 2008;Davey et al, 2011;Sword et al, 2011;Watkins et al, 2011;Figueiredo et al, 2013;Hahn-Holbrook et al, 2013), parity (Green et al, 2006;Glavin et al, 2009;Hamdan and Tamim, 2011;Kozinszky et al, 2011;Sword et al, 2011;Raisanen et al, 2013;Gaillard et al, 2014) and sex of baby (Boyce and Hickey, 2005;de Tychey et al, 2008;Kim et al, 2008;Koutra et al, 2014) showed mixed findings. Women whose infants had medical illnesses (Green et al, 2006;Ueda et al, 2006;Kim et al, 2008;Raisanen et al, 2013), are born prematurely (Raisanen et al, 2013) and are temperamentally difficult (McGrath et al, 2008;Eastwood et al, 2012) are likely to experience postpartum depression.…”
Section: Obstetric and Pediatric Factorsmentioning
confidence: 79%
“…Few studies found younger maternal age as a risk factor (Nakku et al, 2006;Gausia et al, 2009;Bottino et al, 2012), one found the reverse (Kheirabadi et al, 2009) and many found no association (Alami et al, 2006;Moraes et al, 2006; Studies suggest that low socio-economic status contributes to the development of postpartum depression (Goyal et al, 2010). Its determinants of low education level (Chien et al, 2006), low income (Segre et al, 2007;Kim et al, 2008;Kozinszky et al, 2011;Eastwood et al, 2012) and unemployment (Rubertsson et al, 2005) are related to postpartum depression. Other studies have reported no such influence in developed countries (Boyce and Hickey, 2005;Green et al, 2006;Kim et al, 2008;Leigh and Milgrom, 2008;Hamdan and Tamim, 2011;Goker et al, 2012;Deng et al, 2014).…”
Section: Socio-demographic Factorsmentioning
confidence: 94%
See 1 more Smart Citation
“…In the context of Chinese medicine, cold and hot suggest the inherent nature of the food, not the temperature of the food (L. Y. Chien, Tai, Ko, Huang, & Sheu, 2006). Yang food such as chicken, pig's trotters, internal organs, ginseng, and eggs are encouraged to nourish the blood and to facilitate recovery by redressing the Yin-Yang or hot-cold imbalance (Y. C. Chien, Liu, Huang, Hsu, & Chao, 2005;Holroyd et al, 2004;Holroyd, Kate, Chun, & Ha, 1997;Koon, Peng, & Karim, 2005).…”
Section: "Should Do" Activitiesmentioning
confidence: 99%
“…While it is recognized that postnatal confinement protects women against postnatal mental distress, Demirel et al [4] argue that observing some of the traditional practices predisposes women to Chien et al, [7] writing from Taiwan assert that observance of the traditional practices during postpartum confinement accelerates better health for postpartum mothers. Similarly, Chen et al, [8] found that conformity to confinement and rituals in imposed during confinement was negatively associated with postpartum mental distress (OR = 0.93, 95% CI: 0.90 -0.96).…”
Section: Introductionmentioning
confidence: 99%